(untitled) (Nigerian Journal of Cooperative Economics and Management, 2021)
The study investigated the relationship between capacity building and service delivery in the Old Aguata Local Government Area in Anambra State Nigeria. Specifically, the study determined the relationship between staff training and staff competencies; and the relationship between staff competencies and service delivery. Data were collected from 283 randomly selected senior local government staff from Aguata, Orumba North and Orumba South local government areas. Mean, frequency counts and tables were used to present and describe collected data. Also two hypotheses were tested through the application of Pearson Product Moment Correlation at the 0.05 level of significance. Findings revealed that there were significant relationships between staff training and staff competence; and between staff competence and service delivery. The study recommended among others, concerted efforts by local government authorities to ensure that sustainable regular training programs are put in place to ensure that all staff has access to training and re-training opportunities on regular basis